Hubungan Tingkat Kejenuhan Kerja Dengan Stres Kerja Pada Perawat Ruang Rawat Inap Di RSUD Bangkinang - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2023)
Nurses face various aspects in providing services to patients, one of which is the aspect of working conditions. Work saturation is a condition where workers do their daily work. Conducive work saturation will provide a sense of comfort and fun to employees and enable employees to work optimally. Work saturation can affect one's emotions and soul. This study aims to determine the relationship between nurse job burnout and nurse work stress at Bangkinang Hospital in 2023. This study is an analytic study with a cross-sectional design using primary data. The research sample consisted of 35 respondents, namely 17 emergency room nurses and 18 internal nurses. The results of the study showed that there was a relationship between nurse work saturation and nurse work stress with a p value of 0.026. It is recommended to apply periodic work rotations for nurses in the room so that it does not cause boredom for nurses when working in one room for a long time which can cause work stress, besides that work rotation can cause work motivation for nurses. Keywords: Job Saturation, Work Stress, Nurse